What long-term care interventions have been published between 2010 and 2020? Results of a WHO scoping review identifying long-term care interventions for older people around the world. Issue 1 (31st January 2022) - Arias-Casais, Natalia; Amuthavalli Thiyagarajan, Jotheeswaran; Rodrigues Perracini, Monica; Park, Eunok; Van den Block, Lieve; Sumi, Yuka; Sadana, Ritu; Banerjee, Anshu; Han, Zee-A
Abstract : Objective: The global population is rapidly ageing. To tackle the increasing prevalence of older adults' chronic conditions, loss of intrinsic capacity and functional ability, long-term care interventions are required. The study aim was to identify long-term care interventions reported in scientific literature from 2010 to 2020 and categorise them in relation to WHO's public health framework of healthy ageing. Design: Scoping review conducted on PubMed, CINHAL, Cochrane and Google Advanced targeting studies reporting on long-term care interventions for older and frail adults. An internal validated Excel matrix was used for charting. Setting nursing homes, assisted care homes, long-term care facilities, home, residential houses for the elderly and at the community. Inclusion criteria: Studies published in peer-reviewed journals between 1 January 2010 to 1 February 2020 on implemented interventions with outcome measures provided in the settings mentioned above for subjects older than 60 years old in English, Spanish, German, Portuguese or French. Results: 305 studies were included. Fifty clustered interventions were identified and organised into four WHO Healthy Ageing domains and 20 subdomains. All interventions delved from high-income settings; no interventions from low-resource settings were identified. The most frequently reported interventions were multimodal exercise (n=68 reports, person-centred assessment and care plan development (n=22), case management for continuum care (n=16), multicomponent interventions (n=15), psychoeducational interventions for caregivers (n=13) and interventions mitigating cognitive decline (n=13). Conclusion: The identified interventions are diverse overarching multiple settings and areas seeking to prevent, treat and improve loss of functional ability and intrinsic capacity. Interventions from low-resource settings were not identified.